The Influence of Brand Image and Brand Love on Customer Loyalty Mediated by Customer Engagement: Study on Consumers of Wardah Cosmetics - Nurfitriana, Rizqi; Surachman, Surachman; Hussein, Ananda Sabil (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
Industrial cosmetics growth has increased every year. This situation makes a tight competition among the Cosmetic companies. Cosmetic companies try to create customer loyalty so they could sustain their business. Prior studies have examined variables that affect customer loyalty, yet only few studies have examined the effect of brand image, brand love and customer engagement in creating customer loyalty. This study aims to determine the effect of brand image, brand love, and customer engagement on customer loyalty of consumer Wardah Cosmetics in Malang. This study was explanatory with a quantitative approach and survey methode conducted on 150 respondents in Malang. Nonporbability sampling with purposive sampling technique was used. Data analysis process used by Partial Least Square (PLS). Results reveal that brand image and brand love has simultaneously significant effect on customer engagement. Brand love has significant effect on customer loyalty while brand image has no significant effect on customer loyalty. Customer engagement was also found to act as a mediator in this study. The results also reveal that customer engagement influences customer loyalty. The results of this study can prove helpful to practitioners about enhancing loyalty in their company based on brand image, brand love and customer engagement. The result of the research can also be a reference for future research.